Current thermal state of permafrost in the southern Peruvian Andes and potential impact from El Niño–Southern Oscillation (ENSO) - Yoshikawa K. (2020)
Tropical high-mountain permafrost has a unique thermal regime due to its exposure to strong solar radiation and to rough surface snow morphology, which reduce ground heat transfer from the surface. Latent heat transfer and higher albedo that occur during the snow-covered season contribute to positive feedback that supports the presence of permafrost. This preliminary study reports on the thermal state characteristics of tropical mountain permafrost in Peru. This work also evaluates the potential combined impact of the El Niño–Southern Oscillation (ENSO) in the mountain permafrost of the Coropuna and Chachani volcanic complexes, both located at the western edge of the southern Peruvian Altiplano. Temperature monitoring boreholes were established at 5,217 m at Coropuna and 5,331 m at Chachani, and electrical resistivity was surveyed in both sites. This 7-year discontinuous record of permafrost temperature data encompasses historically extreme El Niño/La Niña events. Our results show that the current lower-altitude permafrost boundary (~5,100 m a.s.l.) is critically influenced by the balance of wet and dry seasons: permafrost tends to deplete during drought years. Typical permafrost thickness was 10–20 m and contained ice-rich pore spaces. The presence of permafrost and its thermal resistance depends on ice content and on higher albedo, usually due to: (a) hydrothermal alteration, which transforms the volcanic rocks into surfaces with ideal albedo for permafrost resilience; and (b) sublimation of the snow cover, forming ice-pinnacles named penitentes. © 2020 John Wiley & Sons, Ltd.